2000
DOI: 10.1080/003655200453692
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine or Procaine for Pain Relief in Acute Pancreatitis A Prospective Randomized Study

Abstract: Constant i.v. application of buprenorphine is more effective than the recommended procaine for pain relief in acute pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…We confirm and extend findings from a previously published smaller study that reported procaine to be less effective than buprenorphine in the treatment of pain in patients with AP [7]. Patients with an AP usually suffer from severe abdominal pain and therefore a major treatment goal is rapid onset and potent pain relief.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We confirm and extend findings from a previously published smaller study that reported procaine to be less effective than buprenorphine in the treatment of pain in patients with AP [7]. Patients with an AP usually suffer from severe abdominal pain and therefore a major treatment goal is rapid onset and potent pain relief.…”
Section: Discussionsupporting
confidence: 80%
“…However, there are no prospective trials proving any beneficial effect of intravenously administered procaine on pain in patients with AP. In a recent small study, procaine was proven to be less effective compared to other drugs [7]. We therefore performed a clinical trial to evaluate the efficacy of procaine compared to pentazocine for pain control in patients with AP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no extensive studies on the pharmacological control of pain in acute pancreatitis patients [1,2,3,4], which is quite surprising given the importance of this symptom during the course of the disease. There is also a lack of evidence regarding the degree of efficacy of the various pharmacological substances used to treat the different forms of acute pancreatitis.…”
Section: Introductionmentioning
confidence: 99%
“…In a first trial the effect of procaine on pancreatitis pain was compared to that of opiates and opiates were, not surprisingly, found to be much more effective [3]. The design of this trial, however, could not answer the question whether procaine had any effect on pain at all.…”
Section: Introductionmentioning
confidence: 99%